The hidden in plain sight: global, regional, and national trends in the pediatric burden of Klinefelter syndrome, 1990–2021 - Ma, Guoqian; Li, Yuan; Jia, Fan (Frontiers in Genetics, 2025)
BackgroundKlinefelter syndrome (KS) is the most common sex chromosome aneuploidy in males, but its epidemiology in children and adolescents remains poorly characterized worldwide. This study provides the first comprehensive global, regional, and national assessment of KS prevalence and disability-adjusted life years (DALYs) in individuals under 20 years from 1990 to 2021.MethodsWe extracted data on KS prevalence and DALYs for individuals under 20 years of age from the Global Burden of Disease (GBD) 2021 database, covering 204 countries and territories. We evaluated temporal trends using the estimated annual percentage change (EAPC), stratified by age group, geographic region, and sociodemographic index (SDI) level.FindingsBetween 1990 and 2021, the global number of KS cases in children and adolescents increased from 589,674 (95% UI, 440,342–770,284) to 690,885 (518,462–899,583), a 17.2% rise, while the overall prevalence rate per 100,000 remained stable (26.1 in 1990 to 26.2 in 2021). The global DALY burden attributed to KS rose by 20% over three decades, with marked disparities across SDI levels: in 2021, prevalence rates ranged from 17.1 per 100,000 (low-SDI) to 32.5 per 100,000 (high-SDI), and DALY rates varied from 0.05 to 0.15 per 100,000 across regions. High-SDI countries reported higher prevalence and DALY rates, likely reflecting superior diagnostic capacity and access to genetic services. In contrast, most low- and middle-SDI regions showed minimal changes in prevalence rates, despite increases in absolute case numbers, suggesting persistent underdiagnosis. Notably, children under 1 year of age and adolescents aged 15–19 represented the groups with the highest (49.5 per 100,000) and lowest (17.6 per 100,000) prevalence, respectively.InterpretationKS continues to represent a largely undetected pediatric health burden, especially in low- and middle-SDI settings. The findings highlight the urgent need for enhanced awareness, early detection strategies, and equitable access to genetic services in global child health policy. Timely diagnosis and intervention can help prevent long-term developmental and health-related consequences of KS.